2014
DOI: 10.1007/s10067-014-2758-0
|View full text |Cite
|
Sign up to set email alerts
|

History of knee injury and MRI-assessed knee structures in middle- and older-aged adults: a cross-sectional study

Abstract: The aim of this cross-sectional study was to describe the associations between history of knee injury and knee structure using magnetic resonance imaging (MRI). This study included two population-based samples: the Tasmanian Older Adult Cohort (TASOAC) study (n = 430; mean age, 63.0 years; range, 51-79 years; 51 % female) and the Offspring study (n = 372; mean age, 45.0 years; range, 26-61 years; 57.5 % female). In both studies, 1.5 T MRI scans of the right knee were performed to measure bone marrow lesions (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(45 reference statements)
1
2
0
Order By: Relevance
“…We found that age was associated with increased risk of BMLs, which is consistent with a finding in a non-OA population cohort [ 37 ]. Injury was associated with medial tibiofemoral BMLs, which is in line with the finding observed in middle-aged and older adults [ 38 ]. However, BMI was not significantly associated with BMLs in this young cohort.…”
Section: Discussionsupporting
confidence: 88%
“…We found that age was associated with increased risk of BMLs, which is consistent with a finding in a non-OA population cohort [ 37 ]. Injury was associated with medial tibiofemoral BMLs, which is in line with the finding observed in middle-aged and older adults [ 38 ]. However, BMI was not significantly associated with BMLs in this young cohort.…”
Section: Discussionsupporting
confidence: 88%
“…History of knee injury (e.g. ACL rupture) has been associated with tibiofemoral BMLs [17]. Biomechanical alterations were persistent even after ACL reconstruction [18], and therefore the altered biomechanical forces might be involved in incident or enlarging subchondral BMLs.…”
Section: Discussionmentioning
confidence: 99%
“…History of knee joint injury was assessed using a self-administered questionnaire [ 11 ] which included the following questions: “Have you ever had a previous knee injury which resulted in non-weight bearing treatment for 24 h or more?” “If yes, then which knee?” “Please provide further details about the injury” …”
Section: Methodsmentioning
confidence: 99%